Influence of rurality on general practitioner registrars' participation in their practice's after‐hours roster: A cross‐sectional study. (23rd February 2022) - Morgan, Tobias; Tapley, Amanda; Davey, Andrew; Holliday, Elizabeth; Fielding, Alison; van Driel, Mieke; Ball, Jean; Spike, Neil; FitzGerald, Kristen; Morgan, Simon; Magin, Parker
Abstract: Objective: To investigate whether practice rurality and rural training pathway are associated with general practitioner registrars' participation in their practice's after‐hours care roster. Design: A cross‐sectional analysis of data (2017‐2019) from the Registrar Clinical Encounters in Training study, an ongoing inception cohort study of Australian general practitioner registrars. The principal analyses used logistic regression. Setting: Three national general practitioner regional training organisations across 3 Australian states. Participants: General practitioner registrars in training within regional training organisations. Main outcome measure: Involvement in practice after‐hours care was indicated by a dichotomous response on a 6‐monthly Registrar Clinical Encounters in Training study questionnaire item. Results: 1576 registrars provided 3158 observations (response rate 90.3%). Of these, 1574 (48.6% [95% confidence interval: 46.8‐50.3]) involved registrars contributing to their practice's after‐hours roster. In major cities, 40% of registrar terms involved contribution to their practice's after‐hours roster; in regional and remote practices, 62% contributed to the after‐hours roster. On multivariable analysis, both level of rurality of practice (odds ratio(OR) 1.75, P  = .007; and OR 1.74, P = .026 for inner regional and outer regional/remote locations, respectively, versus major city) and rural training pathway of registrar (OR 1.65, P  = .008) were significantly associated with more after‐hours roster contribution. Other associations were registrars' later training stage, larger practices and practices not routinely bulk billing. Significant regional variability in after‐hours care was identified (after adjusting for rurality). Conclusion: These findings suggest that registrars working rurally and those training on the rural pathway are more often participating in practice after‐hours rosters. This has workforce implications, and implications for the educational richness of registrars' training environment.